An innovation of LH Bites Cookies holder of augmented reality technology and QR code / Syafiqah Jasni ... [et al.] - Jasni, Syafiqah; Mohd Rosnan, Shalida; Hussain, Zawawi; Shamsuddin, Nik Atilla Atasha (Universiti Teknologi MARA, Kedah, 2023)
According to Puan Nurul Hidayah, LH Bites cookies started when the MCO was first enforced, which was in 2019 in a small business. LH Bites Cookies is a company that’s sells premium cookies that has 3 flavours which is Belgium chocolate chip, Red Velvet white chocolate chip and Cranberries Oat cookies. For this packaging, I want to focus on Belgium chocolate chip because of high demand. The products that they sell come in a bottle as their packaging. In order to come out with a better improved packaging, certain criteria need to be fulfilled- easily to hold and bring when buy the product at Mesra@Petronas, it does not have any plastic bag The first objective is to ease customers to bring after purchasing the product at Mesra@Petronas. So, to improve this product branding, it will come out with carrier. Next, to protect the product from damage and breakage. Lastly, to attract customers with the packaging innovation. A combination of Augmented Reality (AR) technology innovation which is can increase the visibility of their products and QR code will continue to display social media LH Bites Cookies if wanted to buy or inquire further. The novelty made for the packaging is upgrading from a bottle to a box packaging. The packaging is able to protect the product from damage and breakage and also to maintain quality of cookies. Matte lamination I have chosen as the packaging finishing. The use of the matte lamination can enhance the look of the packaging, which appeals to the kids as a target.